Hubungan Pola Asuh Orang Tua dan Disiplin Anak Usia 5-6 Tahun di TK Swasta Solo Fide - Rismawati Munthe (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
This study aims to determine the relationship between parenting style and discipline for children aged 5-6 years in Solo Fide Private Kindergarten. The subjects in this study were 42 students of Solo Fide Private Kindergarten. The measuring instrument used in this study is the Likert scale which consists of 21 parenting items ( α = 0.803) and 14 discipline items ( α = 0.698). Data analysis using pearson product moment technique . Based on data analysis, the correlation value between parenting and discipline was obtained by the coefficient rxy = 0.694 with a significant level of 0.000. This shows that the research hypothesis is accepted, namely that there is a significant positive relationship between parenting style and student discipline in Solo Fide Private Kindergarten. Furthermore, seen from the calculation of the empirical mean of parenting is 64.67 and the empirical mean of discipline is 42.93. So it can be concluded that the students of Solo Fide Private Kindergarten are good.